Peningkatan Pengetahuan Konseptual tentang Bangun Datar melalui Pendidikan Matematika Realtistik - Puri Pramudiani; Adinda Fuadillah Oktafiani; Tian Abdul Aziz; Yoppy Wahyu Purnomo (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2017)
This study aims to examine whether there is an increased understanding of the concept of shape using Realistic Mathematics Education. This research was conducted in one primary school class II in the academic year 2016/2017. Design Research was chosen as a basis research which included preparation for the experiment, preliminary teaching experiment class which involved 6 students Class IIA to test early Hypothetical Learning Trajectory (HLT), Teaching Experiment class which involved 37 students of Class IIB, and retrospective analysis (data analysis obtained from the previous stage). HLT plays an important role as a research design and instrument. Learning trajectory that has been designed then was compared with the actual student learning in the teaching experiment. The data of the students’ understanding of the concept of shape was obtained by using pre-test, observation, interview, student worksheet and post-test as well as data obtained in the learning process. The results of this study found that there was an increased understanding of the concept of the shape which will be elaborated further in the discussion.